The Peripatetic Life of a Remittance Man: The Extraordinary W.E. Hamilton - Williams, Donna (Ontario History)

(untitled) (The Ontario Historical Society, 2024)
Nineteenth-century Ontario was home to an army of remittance men, the wayward sons of aristocratic and upper-middle-class Britons who were sent to the colonies, supported by their families to avoid disgrace at home. One such man was W.E. (William Edwin) Hamilton (1834-1902), whose father, the brilliant Irish mathematician, Sir William Rowan Hamilton, sent him to Nicaragua and later Ontario to avoid the embarrassment of his son’s inability to earn a living. Hamilton was self-destructive in many ways, but he eventually found success as a journalist in communities across Ontario, where he settled for the last thirty years of his life. He strived to live up to his family’s expectations, but was seen by many as a failure and was virtually written out of the historical record by his father’s biographers. Nevertheless, he carved out his own rather colourful career, despite being dogged by his personal demons and eccentricities.